Edukasi Santri Dalam Upaya Pencegahan Wabah Virus Covid – 19 Di Pondok Pesantren Sumbersari Kencong Kepung Kediri Jatim - M. Nur Kholiq; Ahmad Hafidz Syafrudin (LP3M IAIFA Kediri, 2021)
This research is a santri education program in an effort to prevent the outbreak of the Covid-19 coronavirus is a virus that causes respiratory tract infections. From several existing sources, this disease is very fast spreading, factors that cause rapid transmission of the disease in pesantren are the number of students in one room, inadequate sanitation and ventilation, and santri confidence in interpreting certain diseases. The research approach used in this study is the PAR or Participatory Action Research method. Participatory Action Research is one of the research models that look for something to connect the research process into the process of social change. The result of this research is that this activity is going well, because in the implementation of this activity we are welcomed by the chairman and board of the cottage, so that every activity of the main work program or individual gets a good feed back from smua santri in ponpes. For the individual activities of the author regarding the provision of emergency wash sinks and handwashing soaps in the guise, also received an enthusiastic welcome by the santri and administrators of some of the cottage devices.